(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2025)
This article offers a comprehensive analysis of the multifaceted roles and rights of women in ancient India, as reflected in Hindu legal texts. It examines how social norms influence women’s lives, from their education and intellectual development to the constraints and expectations that shape their experiences. The study delves into family dynamics, addressing women’s roles and rights within the family, their marital relationships, and controversial practices such as niyoga (levirate) and sati. It also explores the legal aspects of marriage, polygamy, polyandry, and divorce, while considering women’s property rights, inheritance, and maintenance. The article emphasises the progressive elements of gender relations and the rights granted to widows, while also briefly discussing their rights to adoption, guardianship, and maintenance. Overall, it provides a thorough overview of the legal status of women in ancient India, revealing the complexities of their social position. JASBH, Vol. 70(1), June 2025, pp. 1–35